Characterization of a bla(NDM-1)-harboring plasmid from a Salmonella enterica clinical isolate in China - Huang, Jinwei (Mol Med Rep, 2017)
The plasmid-mediated transmission of antibiotic resistance genes has been reported to be involved in the development of antibiotic resistance in bacteria, and poses a serious threat for the success of bacterial infection treatment and human health worldwide. The present study used a 454 GS-FLX pyrosequencing system to determine the ~140 kb nucleotide sequence of plasmid pHS36-NDM, which was identified in a Salmonella Stanley isolate from the stool sample of an 11-month-old girl at Lishui Central Hospital, China, and which contains a New Delhi metallo-β-lactamase-1 (NDM-1) carbapenem resistance gene (bla(NDM-1)). The 181 open reading frames encode proteins with functions including replication, stable inheritance, antibiotic resistance and mobile genetic elements. Both horizontal transfer and passage stability-related genes were identified in pHS36-NDM, including a conserved type 4 secretion system and stbA (stable plasmid inheritance protein A). Two multidrug resistance gene islands were identified: The ISEcp1-bla(CMY) transposition unit which contains a CMY-6 β-lactamase gene (bla(CMY-6)) and a quaternary ammonium compound resistance gene (sugE); and the intI1-ISCR27 accessory region, which contained a trimethoprim resistance gene (dfrA12), two aminoglycoside resistance genes (aadA2 and rmtC), a truncated quaternary ammonium compound resistance gene (qacE∆1), a sulfonamide resistance gene (sul1), the bla(NDM-1) carbapenemase and a bleomycin resistance gene (ble(MBL)). pHS36-NDM shared high homology with other bla(NDM-1)-containing plasmids reported in Sweden, Italy and Japan. However, no previous international travel history was documented for the patient and her family, even to neighboring cities. Furthermore, pHS36-NDM is of a different incompatibility group to other published bla(NDM-1)-carrying plasmids reported in China, with low homology in the surrounding structure of bla(NDM-1). The present study will facilitate the understanding of the underlying resistance and dispersal mechanism of pHS36-NDM, and will deepen our recognition of the ongoing spread of the bla(NDM-1)-containing plasmids.